The Role of Aqidah Ahklak of Teacher in Developing Students' Morals at MTs Ma'arif 06 Seputih Raman - Iman, Nur; Irhamudin, Irhamudin; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to examine the role of the Aqidah Akhlak teacher in developing student morals at MTs Ma'arif 06 Seputih Raman. Good morals are an important aspect in shaping the character of students, so the teacher's role in guiding, instilling moral values, and providing examples is the main factor in the success of moral education. This research uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews and documentation, while data analysis includes the process of data reduction, data display and data verification. The research results show that the Aqidah Akhlak teacher has a very important role in developing students' morals, especially in the aspects of discipline and obedience in worship. Each learning session begins with istighosah together, while students perform midday prayers together in the madrasah hall every day, and get used to praying Dhuha together every Friday. The role of the Moral Creed Teacher in developing student morals includes various aspects, namely as an educator, mediator, role model and motivator